HOUSEHOLD EDUCATION EXPENDITURE AS CORRELATE OF ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENTS IN OSUN STATE, NIGERIA - Akinmoladun, Olarewaju Olakunle,; Akinmoladun, Olarewaju Olakunle, (African Journal of Educational Management, 2021)
This study investigated the influence of household education expenditure (learning materials, transportation, food items and extra lesson expenses) on the academic performance of Senior Secondary School (SSS) students in Osun State, Nigeria. Descriptive research design was adopted. The state was stratified in line with the existing three senatorial districts, with each having 10 local government areas. Four local government areas, representing 40%, were randomly selected from each senatorial district. There were 142 public senior secondary schools in the 12 sampled local government areas. Forty per cent of the schools were randomly selected per local government totaling 56.Random sampling technique was used to select 40% of SSS III students per school, totaling 3,304 Parents and students filled their respective components of the instruments. The instruments titled: “Household Education Expenditure Scale” (r=0.97); “Student English Language Performance Test” (r=0.89) and “Student Mathematics Performance Test” (r=0.88) were used. Five hypotheses were tested (p = 0.05). Data were analysed using Pearson product moment correlation and multiple regression at 0.05 level of significance. Household expenditure on learning materials (r = 0.099; p<0.05), extra lesson (r = 0.169; p<0.05) and transportation (r = 0.16; p<0.05) had significant positive relationship with academic performance while expenditure on food items (r = -0.26; p < 0.05) was negatively related. Household education expenditure on feeding had significant negative contribution to academic performance (? = -0.292; t= -10.050; p<0.05), while expenditure on learning materials had significant positive contribution (? = 0.070; t= 2.909; p<0.05). Others had no significant contributions to academic performance. Household expenditure on learning materials positively influenced academic performance while expenditure on food items had negative influence. The study recommended that household should spend more on learning materials and less on feeding at school to improve academic performance of public secondary school students.